KEKERBATAN BAHASA ANGKOLA DAN BAHASA ACEH: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Iqbal, Muhammad; Nasution, Jamal; Dardanila, Dardanila (Jurnal Dedikasi Pendidikan, 2022)
This study aims to find similarities in meaning and sound, both vowels and consonants between Angkola and Acehnese languages. The method used in this research is a comparative descriptive method. The data compared in this study are 200 basic Swadesh vocabularies between Angkola and Acehnese. The data collection technique used is the note-taking technique. To analyze the data, the lecostatistic technique was used with steps including (1) collecting the basic vocabulary of the language of relatives, (2) determining which pairs of the two languages are related words, calculating the age and time of separation of the languages. The results showed that there were 37 words that were related (18.5%), either words that were identically related or words that experienced changes in vowel and consonant sounds, with details of ten words that were identically related and had the same meaning and the same sound for BAn and BAc ( 5%) and twenty-seven words with sound changes in both vowels and consonants for for BAn and BAc (13.5%). Furthermore, the corresponding words between BAn and BAc are either identical or have very little phoneme change. So that the separation distance until 1982 BC. In general, it can be said that the level of mutual understanding between the Angkola language and the Acehnese language is also very low. Although these two languages come from Austronesian languages